Strategi Pengembangan Usaha Jamur Tiram dengan Analisis SWOT pada Studi Kasus “Warung Jamur Mang Yayat” - Aini Dewi Maryan; Adenty Oktaviani; D Yadi Heryadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Starting a business is an easy job and can be done by anyone, the most important thing is strong beliefs and values ​​for independent business, a strong will to become an entrepreneur is not enough. Good business development starts from ourselves, even though we face many obstacles in the business world, therefore a strategy is needed in business development so that the business can last a long time. One of the current businesses that is very prospective and has potential is cultivating edible mushrooms, one of which is oyster mushrooms which are well known to the public and are a type that has high efficacy.